A Macroscope of English Print Culture, 1530-1700, Applied to the Coevolution of Ideas on Religion, Science, and Institutions - Peter Grajzl; Peter Murrell (Center for Economic Studies and ifo Institute (CESifo), 2023)
We combine unsupervised machine-learning and econometric methods to examine cultural change in 16th- and 17th-century England. A machine-learning digest synthesizes the content of 57,863 texts comprising 83 million words into 110 topics. The topics include the expected, such as Natural Philosophy, and the unexpected, such as Baconian Theology. Using the data generated via machine-learning we then study facets of England's cultural history. Timelines suggest that religious and political discourse gradually became more scholarly over time and economic topics more prominent. The epistemology associated with Bacon was present in theological debates already in the 16th century. Estimating a VAR, we explore the coevolution of ideas on religion, science, and institutions. Innovations in religious ideas induced strong responses in the other two domains. Revolutions did not spur debates on institutions nor did the founding of the Royal Society markedly elevate attention to science.
Keywords: C80; Z10; N00; P10; C30; 330; cultural history; England; machine-learning; text-as-data; coevolution; VAR